A survey and risk assessment of neonicotinoids in water, soil and sediments of Belize. (June 2019) - Bonmatin, Jean-Marc; Noome, Dominique A.; Moreno, Heron; Mitchell, Edward A.D.; Glauser, Gaëtan; Soumana, Oumarou S.; Bijleveld van Lexmond, Maarten; Sánchez-Bayo, Francisco
Abstract: Usage of neonicotinoids is common in all agricultural regions of the world but data on environmental contamination in tropical regions is scarce. We conducted a survey of five neonicotinoids in soil, water and sediment samples along gradients from crops fields to protected lowland tropical forest, mangroves and wetlands in northern Belize, a region of high biodiversity value. Neonicotinoid frequency of detection and concentrations were highest in soil (68%) and lowest in water (12%). Imidacloprid was the most common residue reaching a maximum of 17.1 ng/g in soil samples. Concentrations in soils differed among crop types, being highest in melon fields and lowest in banana and sugarcane fields. Residues in soil declined with distance to the planted fields, with clothianidin being detected at 100 m and imidacloprid at more than 10 km from the nearest applied field. About half (47%) of the sediments collected contained residues of at least one compound up to 10 km from the source. Total neonicotinoid concentrations in sediments (range 0.014–0.348 ng/g d. w.) were about 10 times lower than in soils from the fields, with imidacloprid being the highest (0.175 ng/g). A probabilistic risk assessment of the residues in the aquatic environment indicates that 31% of sediment samples pose a risk to invertebrate aquatic and benthic organisms by chronic exposure, whereas less than 5% of sediment samples may incur a risk by acute exposure. Current residue levels in water samples do not appear to pose risks to the aquatic fauna. Fugacity modeling of the four main compounds detected suggest that most of the dissipation from the agricultural fields occurs via runoff and leaching through the porous soils of this region. We call for better monitoring of pesticide contamination and invertebrate inventories and finding alternatives to the use of neonicotinoids in agriculture. Graphical abstract: Image 1 Highlights: A survey and risk assessment of neonicotinoids in Belize. We measured neonicotinoids in soil, sediment and water in northern Belize Neonicotinoid residue levels were highest in soils of planted crops Frequency of residues declined from soil (68%) to sediment (47%) and water (12%) Concentrations in soil and sediment decreased with distance to field 31% of sediment samples may pose a risk to aquatic invertebrates by chronic exposure Abstract : Neonicotinoid residues found in wetlands of a Neotropical Nature Reserve pose a risk to aquatic invertebrates.